Pengaruh Gaya Kepemimpinan dan Motivasi Terhadap Kinerja Karyawan pada Puslatbang Lan Makassar - Karnila Permata Intan; Uhud Darmawan Natsir; Zainal Ruma (Journal of Management and Creative Business, 2024)
Leadership traits have an important role in human resource management. A leader must apply a leadership style to manage his subordinates and motivate them so that performance increases. This research aims to determine the partial and simultaneous influence of leadership style and motivation on the performance of Puslatbang KMP LAN RI Makassar employees. This research uses data collection using questionnaire and documentation methods. The population and sample in this study were 67 people. The data analysis technique used is multiple linear regression. The results of this research show that leadership style partially has a positive and significant effect on employee performance at the KMP LAN RI Makassar Training Center and motivation partially has a positive and significant effect on employee performance at the Makassar KMP LAN RI Puslatbang Center. Leadership style and motivation simultaneously have a positive and significant effect on employee performance at Puslatbang KMP LAN RI Makassar.